Genetic Divergence in Taramira (Eruca sativa Mill.) (Journal of Oilseed Brassica, 2026)
One hundred and fifty genotypes of taramira (Eruca sativa Mill.) were evaluated to estimate genetic divergence for seed yield and its component characters. All the genotypes and check varieties were grouped in to 10 clusters. Cluster composition indicated that geographic diversity was not related to genetic diversity. Among all the characters, plant height contributed the most towards total D2 followed by number of siliquae per plant and number of seed per siliqua. Cluster 10 had highest mean value for seed yield per plant and number of secondary branches per plant while cluster VII had highest mean value for number of siliquae per plant. On the basis of D2 analysis, nine genetically diverse cluster pairs, 12 genetically diverse and superior genotypes were identified